2000
DOI: 10.1038/sj.ijo.0801207
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obese children have low bone mass and area for their weight

Abstract: OBJECTIVES: To determine whether girls and boys categorized from body mass index (BMI) values as overweight or obese for their age have lower bone mineral content (BMC) or lower bone area in relation to total body weight than children of normal adiposity. DESIGN: Cross-sectional study in a university bone research unit. SUBJECTS: Two hundred girls and 136 boys aged 3 ± 19 y recruited from the general population by advertisement. MEASUREMENTS: Total body BMC (g) and bone area (cm 2 ) measured by dual energy X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
225
6
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(254 citation statements)
references
References 27 publications
14
225
6
8
Order By: Relevance
“…Hydration is increased, and D LT lower, in obese compared with normal weight individuals (Haroun et al, 2005). These differences have been attributed in part to expansion of the extracellular water space (Battistini et al, 1995), which in turn reflects irreversible changes in hemodynamics (Marken Lichtenbelt and Fogelholm, 1999;Leone et al, 2000); but also in part to reduced mineralisation (Goulding et al, 2000). Thus, values for the hydration or D LT obtained from individuals within the normal range of body weight will not transfer successfully to those obese.…”
Section: Discussionmentioning
confidence: 96%
“…Hydration is increased, and D LT lower, in obese compared with normal weight individuals (Haroun et al, 2005). These differences have been attributed in part to expansion of the extracellular water space (Battistini et al, 1995), which in turn reflects irreversible changes in hemodynamics (Marken Lichtenbelt and Fogelholm, 1999;Leone et al, 2000); but also in part to reduced mineralisation (Goulding et al, 2000). Thus, values for the hydration or D LT obtained from individuals within the normal range of body weight will not transfer successfully to those obese.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have shown that obese adults have increased bone density [16,23]. Given the somewhat conflicting results in previous studies showing that obese children either have increased bone density [6,7,15,24,25] or decreased bone density/mass or bone mineral content relative to body size [11,12], it may be that some older obese children could have an increased bone density, similar to the pattern seen in obese adults. The inconsistent association between obesity and fractures of the proximal femur and femoral shaft was the other interesting finding in this study that was different than most of the rest of the data indicating a relationship between increasing obesity and increasing fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…In some reports, obese children with fracture had somewhat higher levels of radial bone mineral content (BMC) (32) while in others, fractured kids had lower BMC. (33,34) Increased risk of fracture in overweight children may be because of greater fall forces or a greater tendency to fall, but other effects of fat on bone maturation have also been invoked as a potential explanation. (1,4) In older adults, the meta-analysis by De Laet and colleagues (11) found that after BMD adjustment there was a small but significant protective effect of higher BMI on hip fracture in women but not in men.…”
Section: Associations Between Bmi and Fracture Risk By Age And Sexmentioning
confidence: 99%